Doppler flowmetry as a tool of predictive, preventive and personalised dentistry - Orekhova, Liudmila Yu (BioMed Central, 2013)
Periodontal lesions are considered a major problem in the global burden of oral diseases due to their high frequency and negative impact on quality of life. Periodontal inflammation is accomplished by a breakdown of microcirculatory function. Early detection of gingival microvessel dysfunction helps diagnose and prevent the progression of initial periodontal pathology. Doppler flowmetry is a useful tool in the diagnosis, monitoring, prognosis and management of periodontal patients which allows access not only of gingival blood flow but also of pulpal microcirculation. Doppler flowmeters might help to realise the ultimate target of predictive, preventive and personalised periodontology tailored with respect to the particular patient. This article highlights the main working principles of laser Doppler flowmeters and the ultrasonic Doppler flowmeters. The advances in blood flow measurement by ultrasonic flowmetry are discussed.